2020
DOI: 10.3390/ijms21207656
|View full text |Cite
|
Sign up to set email alerts
|

Global Analyses of Expressed Piwi-Interacting RNAs in Gastric Cancer

Abstract: Gastric cancer (GC) represents a notable amount of morbidity and mortality worldwide. Understanding the molecular basis of CG will offer insight into its pathogenesis in an attempt to identify new molecular biomarkers to early diagnose this disease. Therefore, studies involving small non-coding RNAs have been widely explored. Among these, PIWI-interacting RNAs (piRNAs) are an emergent class that can play important roles in carcinogenesis. In this study, small-RNA sequencing was used to identify the global piRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Using next-generation sequencing, the only work with piRNAs for PC highlighted the ten most abundant piRNAs with a difference in expression when comparing tumor tissue with normal tissue ( 32 ). Among the piRNAs highlighted in this work, piR-49145 has already been observed with altered expression in gastric cancer samples compared to adjacent tissue ( 69 ).…”
Section: Introductionmentioning
confidence: 72%
“…Using next-generation sequencing, the only work with piRNAs for PC highlighted the ten most abundant piRNAs with a difference in expression when comparing tumor tissue with normal tissue ( 32 ). Among the piRNAs highlighted in this work, piR-49145 has already been observed with altered expression in gastric cancer samples compared to adjacent tissue ( 69 ).…”
Section: Introductionmentioning
confidence: 72%
“…It is worth noting that piRNAs have emerged as another novel class of small non‐coding RNAs with more than 30 000 members in the human genome, which is much greater than that of miRNAs. 9 , 10 Emerging studies suggest that piRNAs and PIWI proteins are also involved in tumorigenesis. 13 For instance, piR‐021285 is associated with the methylation of cancer‐related genes in breast cancer, 28 and PIWIL1‐interacting RNA piR‐017061 inhibits pancreatic cancer by regulating EFNA5.…”
Section: Discussionmentioning
confidence: 99%
“…PIWI‐interacting RNAs (piRNAs) are a type of small non‐coding RNAs with a length of ~30 nucleotides (nt) and more than 30 000 members were described in the human genome. 8 , 9 , 10 Investigation into the role of piRNAs was initially limited to germ cells and gonadal cells during early embryonic development. 11 Recent reports have shown that piRNAs are expressed in a tissue‐specific manner in a variety of human tissues, and regulate key signaling pathways at the transcriptional or post‐transcriptional level.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are several reports concerning their role in the progression of several diseases, especially cancer. The deregulation of piRNAs was reported in various tumors such as gastric [ 2 , 152 ], colorectal [ 153 ], and breast [ 154 ] cancers, being associated with biological processes that contribute to tumor progression and metastasis. Meanwhile, their functions in the central nervous system (CNS) and their roles in the development of neurodegenerative diseases remain poorly understood.…”
Section: Epigenetic Alterations In Parkinson’s Diseasementioning
confidence: 99%
“…However, the molecular mechanisms engaged in the onset and progression of neurodegenerative diseases remain elusive. A complete understanding of the molecular biology of neurodegeneration will benefit the search for biomarkers to be employed in strategies for disease detection and patient management, as seen with the efforts being made towards cancer research [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%